2D organisation of complex organic molecules - Saywell, Alexander (2010)
The self-assembly of two-dimensional molecular systems is of significant interest, offering an insight into the fundamental interactions which drive the formation of complex supramolecular structures. A careful choice of the molecular 'building blocks' for such self-assembled systems potentially allows the design and production of nanoscale architectures with pre-determined geometries and specific chemical functionalities. Within this thesis the two-dimensional structures formed by the self-assembly of complex organic molecules, deposited on an Au(111) surface held in an ultrahigh vacuum (URV) environment, are studied using a combination of scanning tunnelling microscopy (STM), photoelectron spectroscopy (PES), molecular dynamics (MD), and density functional theory (DFT) techniques. A UHV electrospray deposition (URV-ESD) technique is employed to facilitate the introduction of thermally labile molecules into the URV environment. Bi-molecular networks, formed from perylene tetracarboxylic diimide (PTCDI) and melamine, have previously been observed to assemble on the Au(111) surface. Several more complex phases are reported here, as characterised by S'I'M, with the balance between isotropic and anisotropic interactions giving rise to a variety of structures. Chemical functionality may be added to these networks by incorporating functionalised derivatives of PTCDI. Alternative structures produced by altering the shape of the molecular 'building blocks' are also discussed. The URV-ESD technique is demonstrated here to be compatible with the deposition of the fullerene C60,the single molecule magnet Mn12012(02CCR3h6(H20)4 (Mn12(acetate)16), and porphyrin based oligomers (P4 and P6) and polymers (Pn). The URV-ESD of C60on the clean AU(ll1) surface, and on a surface prepatterned with a PTCDI/melamine network, results in similar structures to those previously observed to be produced by sublimation. Mn12(acetate)16 and the porphyrin oligomers and polymers represent complex molecules which are thermally labile and possess, respectively, novel magnetic and electronic properties. Mn12(acetate) 16is observed to form filamentary aggregates due to the anisotropic nature of the molecule-molecule and molecule-substrate interactions, while P4, P6 and Pn form highly ordered close-packed domains driven by the interdigitation of the alkyl chains attached to the porphyrin cores. The findings presented within this thesis demonstrate that self-assembled molecular structures can be understood in terms of intermolecular interactions, and that for systems containing complex molecules the molecule-molecule interaction potential can lead to the formation of novel structures.